Electricity tariff structure optimization - Saad N.M.; Abdullah Z. (Mattingley Publishing, 2023)
Linear programming; Optimization; Sales; Structural optimization; Electricity customers; Electricity tariff; ILOG; Malaysia; Optimization methodology; Optimization procedures; Stochastic; Stochastic optimizations; Shape optimization